THE EFFECTS OF KEFIR RICH IN PROBIOTIC ADMINISTRATION ON SERUM ENZYMES AND PERFORMANCE IN MALE JAPANESE QUAILS - T. Vahdatpour; D. Babazadeh (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to investigate the influence of different levels of Kefir as probiotic origin on performance values and serum enzymes of male Japanese Quails. Total of 180 one-day old male Japanese quail chicks were randomly assigned in 5 treatments and 3 replicates. Group 1 served as control and received normal drinking water. Chicks in group 2, 3, 4 and 5 wereapplied3, 6, 9 and 12 percent Kefirindrinking waterrespectivelyuntil the end of theexperiment(42 days). Consumption of different levels of Kefir showed a decrease on liver weight (P<0.05). Treatment group received 12% Kefir significantly increased heart weight compared to other groups (P<0.05). Treatment groups received 3, 9 and 12 percent Kefir decreased feed intake (P<0.05). Quails received different levels of Kefir increased AST enzyme activity (P<0.05). Using 3% and 6% Kefir caused a decrease in ALP enzyme activity (P<0.05). Results indicated that using lower levels of Kefir revealed more positive effects than higher levels.
Keywords: Kefir; Antioxidant; MDA; Performance; Enzyme; Japanese quail